Hesitation kills a female Marine officer's combat experience in Iraq - Blair, Jane 1972- (Rowman & Littlefield Publishers, 2011)
This riveting memoir is the first book written by a famale Marine about the war in Iraq and one of the only books written by a woman who has experienced combat firsthand.